Angular control of a hybrid magnetic metamolecule using anisotropic FeCo - Gregory, S; Maple, L; Stenning, G; Hesjedal, T; van der Laan, G; Bowden, G (American Physical Society, 2015)
By coupling magnetic elements to metamaterials, hybrid metamolecules can be created with useful properties such as photon-magnon mode mixing. Here, we present results for a split-ring resonator (SRR) placed in close proximity to a thin crystalline film of magnetically hard FeCo. Eddy-current shielding is suppressed by patterning the FeCo into 100-μm disks. At the ferromagnetic resonance (FMR) condition of FeCo, photon-magnon coupling strengths of 5% are observed. Altogether, three distinct features are presented and discussed: (i) remanent magnets allow FMR to be performed in a near-zero field, partially eliminating the need for applied fields; (ii) the anisotropic FMR permits angular control over hybrid SRR and FMR resonances; and (iii) the in-plane and out-of-plane magnetization of FeCo opens the door to “magnetically configurable metamaterials” in real time. Finally, a special study is presented of how best to excite the numerous transverse magnetic and electric modes of the SRR by using near-field excitation from a coplanar waveguide.